Kinerja Keuangan Bank Konvensional dan Bank Syariah (Study pada PT. Bank Negara Indonesia Tbk tahun 2010-2014) - Dian Masita Dewi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This study aims to: (1) Analyze financial performance. Bank Negara Indonesia Tbk. in 2010-2014, (2) analyzing financial performance. Bank Negara Indonesia Syariah Tbk. in 2010-2014, (3) to analyze the differences in the financial performance of conventional banks and Islamic banks in the PT. Bank Negara Indonesia Tbk. 2010-2014. This research is a kind of causal comparative research. Population in this research is PT. Bank Negara Indonesia Tbk. and PT. Bank Negara Indonesia Syariah Tbk. The sample in this research is financial statements from 2010-2014 PT. Bank Negara Indonesia Tbk. and PT. Bank Negara Indonesia Syariah Tbk. This study uses secondary data. Secondary data in this study were obtained from the annual financial report of PT. Bank Negara Indonesia Tbk. and PT. Bank Negara Indonesia Syariah Tbk. on during the period 2010-2014 that has been audited and publicized to the public via the official website of PT. Bank Negara Indonesia Tbk. and PT. Bank Negara Indonesia Syariah Tbk. This research assessment system uses a quantitative approach. Quantitative approach carried out by calculating financial ratios and the ratios are NPL, LDR, ROA, And CAR which is then followed by different test by using statistical test Independent Sample t - Test. The results showed that there were significant differences in financial performance between conventional banks and Islamic banks during the period 2010-2014. In general, in terms of liquidity, profitability, and capital of the Bank Negara Indonesia's financial performance is better than the Bank Negara Indonesia Syariah. Bank Negara Indonesia Syariah only have better asset quality of the Bank Negara Indonesia.